DEEP OXDATION OF CHLORINE-CONTAINING ALKANES IN HETEROGENEOUS OXIDE CATALYSTS - Білокопитов, Ю. В.; Гаєвська, Т. А.; Бурлаченко, Є. С. (Science-based technologies, 2009)
In work influence of connection energy of oxygen with a surface of the oxide catalyst and processes of formation and destruction of superficial metal chlorides on a course of heterogeneous-catalytic xidation of chlorine-containing alkanes are investigated. Influence of quantity of chlorine atoms in chloroalkanes on their reactionary ability is investigated. The catalyst and conditions of carrying out of the deep heterogeneous-catalytic oxidation of chlorine-containing alkanes up to СO2, HCl, Cl2 is offered, that can find an application in the industry at neutralization of chlororganic waste products.